Landseer’s Highlands : a Place of Fascination with the “Monarchs of Nature” - Vicente, Sara (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2019)
The English animal painter Sir Edwin Landseer (1802-1873) first visited the Highlands in 1824 and, from that moment on, his artistic career was to be unavoidably marked by his profound fascination with the romantic sights he encountered there. The artist’s empathy with the wild animals that inhabited the Scottish landscape functioned as a pretext for him to travel to the Highlands annually along with his friend Charles Leslie (1794-1859), also a renowned painter, who introduced Landseer to one of his favourite writers, Sir Walter Scott (1771-1832), whose home at Abbotsford the artist began visiting regularly. Despite their growing attractiveness, these journeys also served a practical purpose. They contributed to developing methods for the accurate observation of animals in loco in order to capture their body language at particular moments of joy (Highland Music, 1829) and suffering (Highland Nurses, 1856), thereby demonstrating that their feelings and expressions are akin to ours. These empiricist observations also allowed Landseer to depict the struggle for survival of many species in danger of extinction through his studies of dead game and sporting scenes. Among these are some of his best known works such as The Hunting of Chevy Chase (1825-1826), Stag at Bay (1846) and The Monarch of the Glen (1851). We must highlight that during these visits to Scotland, the artist increased his circle of future clients among a new class of entrepreneurial collectors. Due to his reputation as the foremost animal painter of his time, Landseer soon became one of Queen Victoria’s favourite artists. The Queen was captivated by his art and commissioned him to paint the royal family and their beloved pets on several occasions. Thus, Edwin Landseer’s finely detailed portrayals of Scottish culture show us a place of contrasts, where visual images of tragedy and death are entwined with those of a peaceful life in the fascinating Highlands.